Development and validation of the HPLC–MS/MS method and its application to the pharmacokinetic study for the Mongolian drug Sendeng-4 in rat blood plasma - Bai, Pu; Dong, Yu (Frontiers in Pharmacology, 2025)
AbstractSendeng-4 is a Mongolian drug. The Mongolian people have been using it to treat rheumatoid arthritis. At present, an increasing number of Han people are paying attention to the anti-rheumatoid effect of Sendeng-4. However, information on the pharmacokinetics of Sendeng-4 is limited, which limits its wide application in China.ObjectiveLiquid chromatography–tandem mass spectrometry (LC–MS/MS) was established to study the pharmacokinetics of Sendeng-4.MethodMS/MS with a negative ionization mode (ESI-) and multiple reaction monitoring at m/z 300.95→193.09 and 317.08→192.10 were detected for (2R, 3R)-dihydromyricetin and myricetin, respectively. The pharmacokinetic parameters were analyzed by DAS 2.0.ResultThe results showed that the plasma concentration time (C–T) curves of (2R, 3R)-dihydromyricetin and myricetin showed double peaks. The Tmax value of (2R, 3R)-dihydromyricetin and myricetin in both groups was 3 h. In absorption, the AUC(0-∞) values of (2R, 3R)-dihydromyricetin and myricetin in the normal group and the arthritis model group were 16.151 ± 2.670 mg·h/L vs. 11.331 ± 0.749 mg·h/L and 2.626 ± 0.400 mg·h/L vs. 2.213 ± 0.388 mg·h/L, respectively. In the distribution, the Vz/F values of (2R, 3R)-dihydromyricetin and myricetin in the normal group and the arthritis model group were 8.212 L/kg vs. 1.744 L/kg and 5.252 L/kg vs. 10.568 L/kg, respectively. In metabolism, the MRT (0-∞) values of (2R, 3R)-dihydromyricetin and myricetin in the normal group and the arthritis model group were 6.848 h vs. 3.476 h and 5.661 h vs. 8.959 h, respectively. In excretion, the CLz/F values of (2R, 3R)-dihydromyricetin and myricetin in the normal group and the arthritis model group were 0.021 vs. 0.024 L/min/kg and 0.018 vs. 0.021 L/min/kg, respectively. There were significant variations in the absorption levels, distribution levels, and elimination rate of (2R, 3R)-dihydromyricetin and myricetin after the administration of Sendeng-4.ConclusionThe study laid the foundation for the subsequent study of pharmacokinetics of Sendeng-4 in humans. The results of this study will contribute to a better understanding of the activity and clinical application of Sendeng-4 and other related traditional Mongolian drug prescriptions.